Load models support sustainable: planning for Brazil s reservoir aquaculture - David, Gianmarco Silva; Carvalho, Edmir Daniel [UNESP]; Ramos, Igor Paiva [UNESP]; Silva, Reinaldo José da [UNESP]; Silveira, Alexandre Ninhaus [UNESP]; Yasumaru, Fanny; Ribeiro, Caio Cesar; Lemos, Daniel (My University, 2011)
Cage aquaculture in hydroelectric reservoirs has great potential for expansion in Brazil, but there are concerns of negative environmental impacts. The environmental sustainability of cage culture depends on hamornization between farming practices and the hydrological peculiarities of the site. Mass balance modeling can estimate the amounts of nutrients that can be loaded without triggering eutrophication and resulting maximum allowable production volume. Careful climate zoning can also assist proper siting.
Keywords: Fish farming; Environmental impact; Chavantes reservoir; Ilha Solteira reservoir; Environmental carrying capacity